2011
DOI: 10.1073/pnas.1014168108
|View full text |Cite
|
Sign up to set email alerts
|

Spatial segregation of BDNF transcripts enables BDNF to differentially shape distinct dendritic compartments

Abstract: BDNF is produced from many transcripts that display distinct subcellular localization, suggesting that spatially restricted effects occur as a function of genetic and physiological regulation. Different BDNF 5′ splice variants give a restricted localization in the cell body or the proximal and distal compartments of dendrites; however, the functional consequences are not known. Silencing individual endogenous transcripts or overexpressing BDNF-GFP transcripts in cultured neurons demonstrated that whereas some … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
222
0
3

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 179 publications
(241 citation statements)
references
References 44 publications
16
222
0
3
Order By: Relevance
“…Evidence that different Bdnf transcripts are directed to distinct subcellular compartments following neural activity supports the view that these transcripts serve unique, or only partially overlapping, functions Baj et al, 2012;Baj et al, 2011;Lau et al, 2010;Pattabiraman et al, 2005). In rodents, differential production of Bdnf splice variants has been documented in a number of models of neurological and neuropsychiatric disease and in response to various pharmacological treatments (Dias et al, 2003;Fumagalli et al, 2012;Nair et al, 2007;Zuccato et al, 2001).…”
Section: Introductionmentioning
confidence: 62%
See 1 more Smart Citation
“…Evidence that different Bdnf transcripts are directed to distinct subcellular compartments following neural activity supports the view that these transcripts serve unique, or only partially overlapping, functions Baj et al, 2012;Baj et al, 2011;Lau et al, 2010;Pattabiraman et al, 2005). In rodents, differential production of Bdnf splice variants has been documented in a number of models of neurological and neuropsychiatric disease and in response to various pharmacological treatments (Dias et al, 2003;Fumagalli et al, 2012;Nair et al, 2007;Zuccato et al, 2001).…”
Section: Introductionmentioning
confidence: 62%
“…It will also be important to determine the subcellular localization of individual Bdnf transcripts in different brain regions, cell types, and subcellular compartments in vivo. Previous studies in hippocampal cultures demonstrated spatial segregation of Ex1/4 transcripts in proximal dendrites and Ex2/6 transcripts in distal dendrites (Baj et al, 2011). It will be necessary to extend these findings to brain regions containing diverse cell types, such as the HYP, as this may represent another mechanism by which individual Bdnf transcripts may execute diverse functions within a single brain region or neuronal population.…”
Section: Discussionmentioning
confidence: 99%
“…The CPE-like elements are apparently required for both constitutive and activity-dependent localization of the transcript in dendrites (Oe and Yoneda, 2010). In separated studies, the destination of BDNF mRNA was, ultimately, ruled by the presence of 5 0 UTR exons (Baj et al, 2011;Chiaruttini et al, 2009). The selective localization of several 5 0 UTR splice variants in dendrites was coupled to local TrkB activation and differentially modulates dendritic complexity (Baj et al, 2011).…”
Section: Dendritic Targeting Of Bdnf Mrnamentioning
confidence: 99%
“…In separated studies, the destination of BDNF mRNA was, ultimately, ruled by the presence of 5 0 UTR exons (Baj et al, 2011;Chiaruttini et al, 2009). The selective localization of several 5 0 UTR splice variants in dendrites was coupled to local TrkB activation and differentially modulates dendritic complexity (Baj et al, 2011). Importantly, blocking the dendritic localization of BDNF mRNA in vivo reduced BDNF protein levels in dendrites and resulted in deficits in dendritic spine pruning and enlargement .…”
Section: Dendritic Targeting Of Bdnf Mrnamentioning
confidence: 99%
See 1 more Smart Citation